TELEMEDICINE SERVICES IN PERSONAL DATA PROTECTION (LEGAL REVIEW) - Harianto; Marice Simarmata; Irsyam Risdawati (RADJA PUBLIKA, 2025)
The development of digital technology has driven significant transformation in healthcare services, one of which is through the implementation of telemedicine between healthcare facilities. Telemedicine provides easy access to medical services, especially in remote areas, by utilizing information technology for consultation, diagnosis, and clinical data exchange. This study aims to analyze and examine legal regulations regarding personal data protection and the responsibility of telemedicine providers in protecting patients' personal data. The research method used is a normative legal research method, also known as doctrinal legal research or dogmatic legal research. This study focuses on written regulations, so it is closely related to a literature study. The results of the study confirm that to ensure that personal data is managed very carefully and cautiously by telemedicine service providers, more serious sanctions can be considered in this case, namely criminal liability for telemedicine service providers as controllers of personal data in the event that personal data is distributed illegally from management activities carried out using Hans Kelsen's legal liability theory, which states